2021
DOI: 10.1186/s12913-021-07054-3
|View full text |Cite|
|
Sign up to set email alerts
|

Health facility preparedness of maternal and neonatal health services: a survey in Jumla, Nepal

Abstract: Background Over the past 20 years, Nepal has seen major improvements in childhood and maternal survival. In 2015, the Nepalese government introduced a new federal political structure. It is unclear how this has affected the health system, and particularly, maternal and child health care. Hence, this study aims to describe and analyse health facility preparedness in the light of the federalization process with regards to providing appropriate and timely maternal and neonatal health services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…poor general readiness were consistent with the previous study conducted in Karnali province, which showed shortage of medicine for women and newborns [43] and many low and low income countries of South Asia and Africa [44]. Competent staff and equipment availability are important components of health facility readiness for quality service delivery [45].…”
Section: Plos Global Public Healthsupporting
confidence: 86%
See 1 more Smart Citation
“…poor general readiness were consistent with the previous study conducted in Karnali province, which showed shortage of medicine for women and newborns [43] and many low and low income countries of South Asia and Africa [44]. Competent staff and equipment availability are important components of health facility readiness for quality service delivery [45].…”
Section: Plos Global Public Healthsupporting
confidence: 86%
“…These are crucial to identifying and managing potential pregnancy and childbirth complications. In addition, availability of trained workforces, equipment, and laboratory services helps build trust with the health system and increase the service users' engagement with the system [43,49]. Thus, local health system authorities need to identify competent staff and equipment availability in their catchment health facilities and ensure optimal health system readiness.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Like Madhesh province, previous studies showed that women of Karnali province had poor access to health services and received poor quality of care from the health facilities [ 78 – 80 ]. Karnali province is geographically inaccessible with difficult geographic terrain and transportation system, poor health infrastructure for better health services delivery [ 79 ]. Contrarily, our analysis revealed that health facilities of Gandaki province provided better quality antenatal care services.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has emphasised on infrastructural development, supply of essential drugs and equipment, skilled health workforce and guideline-based management for improving the quality of care in the facilities (34,35) . To that end, provision of essential medicines, a stock of necessary equipment and supplies, development of existing infrastructure and appropriate training of healthcare staff may help to overcome the gaps in relation to facility preparedness (29,36) .…”
Section: Discussionmentioning
confidence: 99%